2013
DOI: 10.13005/ojc/290161
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Spectral Studies of Gold Complex with Gliclazide, An Oral Antidiabetic Allopathic Drug

Abstract: Synthesis, characterization and spectral studies of gold complex with gliclazide, an oral antidiabetic drug have been studied. The conductometric titration using monovariation method indicate that complexes are non-ionic and L 2 M type. Analytical data agrees with the molecular formula(C 15 H 20 N 3 O 3 S) 2 Au. Structure of complex was assigned tetrahedral, supported by IR, 1 H-NMR.X-Ray and Mass studies. Structure (II) is proposed for complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(7 reference statements)
2
7
0
Order By: Relevance
“…The powder XRD result of this crystal was compared with previous reports in which urea and L-valine were mixed with acids and metals. From the XRD peak intensity it is concluded that in the present work crystalline nature was very high while comparing previous reports [10][11][12][13][14][15] .…”
Section: Powder Xrdsupporting
confidence: 85%
“…The powder XRD result of this crystal was compared with previous reports in which urea and L-valine were mixed with acids and metals. From the XRD peak intensity it is concluded that in the present work crystalline nature was very high while comparing previous reports [10][11][12][13][14][15] .…”
Section: Powder Xrdsupporting
confidence: 85%
“…From the crystallographic data [21][22][23][24][25][26] unit cell parameters are obtained for Ni complex which attributed to orthorhombic crystal system. The particle size of pioglitazone-nickle complex is 19.871 microns respectively, which is calculated from X-ray line broadening using the Scherrer formula;…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…The molar conductance was measured with digital conductivity meter (HPG system G-3001) using a Digital conductivity bridge in DMF and DMSO at 10 -3 M dilution at room temperature. Magnetic susceptibility was determined by Gouy's balance [13] using CuSO 4 .5H 2 O as calibrant. The electronic spectra of the complexes were recorded by Beckmann-DU-Spectrophotometer (Fullerton, California 92834-3100, USA).…”
Section: Physical Measurementmentioning
confidence: 99%
“…It is known that the existence of metal ions bonded to biologically active compounds may increase their activities [11][12][13][14] . In recent years, because of new interesting applications found in the field of medicine, the metal complexes with tridentate O, N, N types of alternative structures have attracted the attention of chemist.…”
mentioning
confidence: 99%